Children’s Visual Worlds: Participatory Photography as a Lens for Understanding Young Children’s Visual Arts Experiences - Probine, Sarah (Walter de Gruyter GmbH, 2026)
This article explores how participatory photography can offer new ways of understanding children’s visual lives, interests, and meaning-making in early childhood education. It draws from a doctoral study that investigated children’s experiences of visual arts learning in three early childhood settings in Aotearoa New Zealand. While the broader project used a range of participatory and qualitative methods with teachers, children, and families, this article focuses specifically on the methods used with young children. Six participants and their families across the three ECE settings were invited to document their visual experiences at home using digital cameras, offering insights into what held significance in their visual and material worlds. The article shares the narratives of three children, four-year-old twins Ellie and Sydney, and four-year-old Finn, to illustrate how child-led visual storytelling can challenge adult-centric research norms and foreground children’s agency, creativity, and rights. Framed by an interpretivist, narrative orientation, it concludes by considering the ethical and methodological implications of positioning children as co-researchers and argues that participatory visual methods can meaningfully value children’s voices, identities, and lived experiences, contributing to debates on children’s rights (UNCROC Articles 12 and 31), visual literacy, and methodological justice in early childhood research.
Keywords: 3901 Curriculum and pedagogy; visual knowledge creation and critique; participatory visual methods; early childhood education; visual arts; children’s agency; photography; narrative inquiry